Insecurity And Tax Revenue Mobilization In Mali - Souleymane OUONOGO; Sory DOLO; ISSOUFOU SOUMAILA MOULEYE; Aminata KEITA (African Scientific Journal, 2024)
Abstract Mali has been in the grip of a security crisis for several years. This situation has led to the closure of businesses and the relocation of the tax administration to the south of the country. The aim of this article is to study the impact of insecurity on tax revenue mobilization in Mali. The methodological approach used to achieve this objective is the Autoregressive Distributive Lag (ARDL) model. The data are for the period 1990-2021, and the results show that security conflicts significantly affect tax revenue mobilization in Mali over the long term. In the short term, they have no influence on tax revenue mobilization. Control variables such as the lagged values of one and two periods and the current and past share of industry in GDP have a positive and significant impact on tax revenue mobilization in Mali. In view of these results, peace must be promoted as the guarantor of security. Key words: Conflict, tax revenue, ARDL. Résumé Le Mali est en proie depuis plusieurs années avec une crise sécuritaire. Cette situation a provoqué la fermeture des commerces et le déplacement de l’administration fiscale vers le Sud du pays. L’objectif de cet article est d’étudier l’incidence de l’insécurité sur la mobilisation des recettes fiscales au Mali. L’approche méthodologique utilisée pour atteindre cet objectif est celle du modèle Autorégressif Distributif Lag (ARDL). Les données sont de la période 1990-2021.Les résultats montrent que les conflits sécuritaires nuisent significativement à la mobilisation des recettes fiscales au Mali à long terme. A court terme, ils n’ont pas d’influence sur la mobilisation des recettes fiscales. Les variables de contrôle telles que les valeurs retardées d’une et deux périodes, la part courante et passée de l’industrie dans le PIB agissent positivement et significativement sur la mobilisation des recettes fiscales au Mali. Au regard de ces résultats, il faut promouvoir la paix qui est le garant de la sécurité. Mots clés : Conflit, recette fiscale, ARDL.